Cerebrospinal fluid macrophage response to experimental cryptococcal meningitis: relationship between in vivo and in vitro measurements of cytotoxicity. - Perfect, J R (1988)
The functional abilities of macrophages from cerebrospinal fluid (CSF) have so far been little studied. We examined the acquisition of activation characteristics by CSF macrophages during the course of experimental cryptococcal meningitis. CSF macrophages developed the ability for increased reactive oxidative intermediate (H2O2) production and tumor and fungal cytotoxicity. Despite having been activated, CSF macrophages could not inhibit the growth of Cryptococcus neoformans in vitro. Immunosuppression with cyclosporine, which eliminates the natural resistance of rabbits to cryptococcal meningitis, did not prevent or diminish H2O2 production by CSF macrophages but did reduce their tumoricidal activity. Activation of CSF macrophages appears to be an integral part of the central nervous system immune response to C. neoformans in this model, but alone is insufficient to eliminate C. neoformans from the central nervous system.